Histopathological image analysis in medical decision making - Dey, Nilanjan, 1984-; Ashour, Amira, 1975-; Kalia, Harihar; Goswami, R. T.; Das, Himansu (IGI Global, 2019)
"This book addresses the major techniques of segmentation, features extraction and classification, and pattern recognition for the histopathological images as well as their use to support computer-aided systems. It also introduces the analysis of the histopathological images using artificial neural network and other machine learning techniques"--Provided by publisher.